A History of Symbolic Violence: A Spatial Temporal Exploration of the Cultural Capital Legacy of Bengali Pedagogy. (January 2022) - Aziz, Abdul
This study explores historic class-based obstacles in the dispensation of secular pedagogy in the Bengal region with the objective of presenting a better understating of the present pedagogical positioning of the British Bangladeshi diaspora of Tower Hamlets. This study charts the visitation of symbolic violence in the historical development of pedagogy under colonial rule and continues into the East Pakistan period. Through the application of Pierre Bourdieu's primary thinking tools the discussion asserts Muslim Bengalis were educationally marginalised by both colonialists and local elites in the realisation of human capital consumption.